Transcriptomic profiling of human endothelial cells infected with venezuelan equine encephalitis virus reveals NRF2 driven host reprogramming mediated by omaveloxolone treatment - Rezapour, Mostafa; Opoku, Lorreta A.; Trefry, Stephanie V.; Alili, Abbas; Konadu, Maame; Dionisio, Maria Galarza; Gurcan, Metin Nafi; Narayanan, Aarthi (Frontiers in Genetics, 2025)
IntroductionVenezuelan Equine Encephalitis virus (VEEV) is a mosquito-borne alphavirus that causes neurotropic disease with significant morbidity and mortality, especially in children. While interferon-stimulated genes (ISGs) are central to host defense, therapeutic modulation of host responses remains underexplored. Omaveloxolone (OMA), an FDA-approved NRF2 activator, has been proposed as a candidate for host-directed antiviral therapy.MethodsWe investigated transcriptomic responses of human umbilical vein endothelial cells (HUVECs) infected with VEEV TC-83 in the presence or absence of OMA at 24 hours post-infection using RNA-Seq. Differential expression analysis was performed with Generalized Linear Model with Quasi-Likelihood and Magnitude-Altitude Scoring (GLMQL-MAS), followed by Cross-MAS to distinguish shared and condition-specific programs.ResultsUntreated VEEV infection induced a canonical ISG signature including IFIT1-3, OASL, RSAD2, and MX1, together with cytokine and chemokine signaling (IL6, CXCL10, CXCL11), consistent with a strong proinflammatory and antiviral state. In contrast, OMA treatment elicited a broader shift, with 729 upregulated and 1,264 downregulated genes. Key OMA-induced genes (HMOX1, NQO1, GCLM, TXNRD1, SLC7A11) mapped to NRF2-dependent antioxidant, ferroptosis resistance, and detoxification pathways, accompanied by widespread repression of histone cluster genes. Cross-MAS revealed 695 OMA-unique upregulated genes, 86 untreated-unique genes, and 34 shared genes forming a compact interferon-centered antiviral backbone. Network analyses highlighted NRF2-driven antioxidant modules under OMA and cytokine-chemokine modules under untreated infection.DiscussionThese findings demonstrate that OMA redirects host transcription from an interferon-centric, inflammatory response toward an NRF2-driven cytoprotective program while preserving core antiviral mechanisms, which supports NRF2 activation as a therapeutic strategy against VEEV.